Transition metals in angiogenesis – A narrative review - Johannes Dürig; Maurizio Calcagni; Johanna Buschmann (Materials Today Bio, 2023)
The aim of this paper is to offer a narrative review of the literature regarding the influence of transition metals on angiogenesis, excluding lanthanides and actinides. To our knowledge there are not any reviews up to date offering such a summary, which inclined us to write this paper. Angiogenesis describes the process of blood vessel formation, which is an essential requirement for human growth and development. When the complex interplay between pro- and antiangiogenic mediators falls out of balance, angiogenesis can quickly become harmful. As it is so fundamental, both its inhibition and enhancement take part in various diseases, making it a target for therapeutic treatments. Current methods come with limitations, therefore, novel agents are constantly being researched, with metal agents offering promising results. Various transition metals have already been investigated in-depth, with studies indicating both pro- and antiangiogenic properties, respectively. The transition metals are being applied in various formulations, such as nanoparticles, complexes, or scaffold materials. Albeit the increasing attention this field is receiving, there remain many unanswered questions, mostly regarding the molecular mechanisms behind the observed effects. Notably, approximately half of all the transition metals have not yet been investigated regarding potential angiogenic effects. Considering the promising results which have already been established, it should be of great interest to begin investigating the remaining elements whilst also further analyzing the established effects.